Optimization of the Boron Back Surface Field Produced with Reduced Thermal Steps in Bifacial PERT Solar Cell - Thais Crestani; Izete Zanesco; Adriano Moehlecke; Lucas Teixeira Caçapietra Pires da Silva; João Victor Zanatta Britto (Energies)
Bifacial solar cells are the leading technology, and the number of steps in the manufacturing process influences the processing time and production cost. The goal of this paper is to optimize the boron back surface field (B-BSF) produced with reduced thermal steps and to analyze its influence on the electrical parameters and bifaciality coefficients of p-type bifacial PERT solar cells. The boron diffusion and a silicon oxide layer grown as a phosphorus diffusion barrier were carried out in a single thermal step, according to the patent granted BR102012030606-9. The sheet resistance of the emitter and B-BSF were not affected by the reduced thermal steps, demonstrating the effectiveness of the silicon oxide layer as a barrier to phosphorus diffusion in the boron-doped side. The short-circuit current density with incident irradiance on the boron-doped side was impacted by the B-BSF sheet resistance, affecting the efficiency and the maximum power bifaciality coefficient. The high recombination in the pp+ region limited the maximum power bifaciality coefficient to approximately 0.7, which is typical in p-type solar cells. Considering the achieved results, the boron and phosphorus diffusion performed with reduced thermal steps produces bifacial p-PERT solar cells with typical bifaciality, avoiding two thermal steps for silicon oxide growth and chemical etching and cleaning.